Analysis of Local and International Patents for the Microfiltration Process of Various Types of Red Wine Materials - Kakabadze, Elene; Bibileishvili, George; Javashvili, Zaza; Tananashvili, Leila; Mamulashvili, Manana; Butkhuzi, Tinatin; Gogiberidze, Ia (Georgian Scientists, 2025)
Analysis of some issues of local and international patents related to methods of obtaining and purifying various types of red wine materials through the microfiltration process determines the consideration of technologies, techniques, basic technical levels and prototypes created by local and international researchers for the scientific research work of the Institute.